2018
DOI: 10.1021/acs.jpclett.8b01693
|View full text |Cite
|
Sign up to set email alerts
|

Langevin Approach to Modeling of Small Levitating Ordered Droplet Clusters

Abstract: A self-assembled cluster of microdroplets levitating over a heated water surface is a fascinating phenomenon with potential applications for microreactors and for chemical and biological analysis of small volumes of liquids. Recently, we suggested a method to synthesize a cluster with an arbitrary number of small monodisperse droplets. However, the interactions, which control the structure of the cluster, are still not well understood. Here we propose a Langevin computational model considering the aerodynamic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 26 publications
1
14
0
Order By: Relevance
“…However, recent experiments with the cluster in an external electric field of different polarities have shown that the effect of the electrostatic force is negligible in comparison with that of the aerodynamic force [3]. Numerical simulations with the Langevin method taking into account droplet repulsion and random diffusion have also shown results similar to the experimental observations [35].…”
Section: Self-organized Levitating Droplet Clusterssupporting
confidence: 61%
“…However, recent experiments with the cluster in an external electric field of different polarities have shown that the effect of the electrostatic force is negligible in comparison with that of the aerodynamic force [3]. Numerical simulations with the Langevin method taking into account droplet repulsion and random diffusion have also shown results similar to the experimental observations [35].…”
Section: Self-organized Levitating Droplet Clusterssupporting
confidence: 61%
“…An experimentally observed droplet cluster levitates in the center of the low-pressure region bounded by a local heating spot. The pressure is higher on the rim of this region rather than in its center so that the cluster is locked in a potential well (Fedorets et al 2019a;Aktaev et al 2018). Inside this well, the air humidity changes with height above the water surface.…”
Section: Diffusional Termmentioning
confidence: 97%
“…Even more interesting phenomena where the theory of networks can be applied are small droplet clusters [ 23 , 24 , 25 , 26 , 27 ] and small colloidal crystals. Self-assembled clusters of condensed microdroplets (with the typical diameter of dozens of microns) are formed in an ascending flow of vapor and air above a locally heated thin (approximately 1 mm) layer of water.…”
Section: Network In Colloidal Science: Granular Material Colloidmentioning
confidence: 99%